Association between cardiorespiratory fitness and risk of all‐cause and cause‐specific mortality. (29th March 2022) - Zhao, Yang; Sun, Haohang; Qie, Ranran; Han, Minghui; Zhang, Ming; Shi, Xuezhong; Yang, Yongli; Lu, Jie; Hu, Dongsheng; Sun, Liang
Abstract: Objective: The association of cardiorespiratory fitness (CRF) with all‐cause and cause‐specific mortality remains unclear in Chinese population. This study aimed to evaluate the risk of all‐cause, cardiovascular disease (CVD), cancer and other‐cause mortality in Chinese adults using estimated CRF (eCRF). Patients and Methods: We analysed data for 15, 566 participants aged ≥20 years recruited in The Rural Chinese Cohort Study during 2007 to 2008 and followed for mortality during 2013 to 2014. eCRF was calculated with sex‐specific longitudinal non‐exercise algorithms. Cox proportional‐hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for all‐cause and cause‐specific mortality risk according to baseline eCRF. Results: During a median of 6.01 years of follow‐up, 859 deaths occurred, including 359 from CVD, 221 from cancer, and 279 from other causes. Each 1 metabolic equivalent increment in eCRF was associated with decreased risk of all‐cause mortality (men: HR 0.70, 95% CI [0.66–0.74]; women: 0.59, [0.54–0.64]); CVD mortality (men: 0.70 [0.64–0.77]; women: 0.55, [0.48–0.62]); and other‐cause mortality (men: 0.68 [0.62–0.75]; women: 0.57, [0.49–0.66]). The area under receiver operating characteristic curve was significantly higher for eCRF than its modifiable components (waist circumference, body mass index and resting heart rate) in predicting all‐cause and cause‐specific mortality incidence (all p < .001). Conclusion: eCRF was inversely associated with all‐cause, CVD and other‐cause mortality.